Design of an Electric Elevator Drive with High Riding Quality under Jerk Control - Ali, Ali Abdulkareem; Ben Salem, Fatma; Mohammed, Jamal A.-K. (Engineering, Technology & Applied Science Research, 2024)
Sudden movements during the start and stop of electric elevators, known as jerks, can cause discomfort for passengers and negatively affect the performance and lifespan of their mechanical and electrical subsystems. Modern drives cannot directly regulate jerk, necessitating the development of methods to mitigate its effects. This study focuses on designing optimal S-curve motion profiles to reduce jerk in elevator systems driven by an induction motor. The motor operates according to these profiles when integrated with a TMS320F28335 Digital Signal Processor (DSP) under Direct Torque Control (DTC). Precise motor control is achieved using an incremental rotary encoder, current sensors, and voltage sensors, while an accelerometer sensor connected to an Arduino Nano measures the jerk. This comprehensive approach ensures precise regulation, smooth performance, and minimal sudden changes in acceleration, highlighting the effectiveness of DTC combined with S-curve profiles in enhancing elevator system performance. The results demonstrate that integrating S-curve profiles into the DTC algorithm significantly improves ride comfort by mitigating jerk during acceleration and deceleration phases by up to 57.2% compared to systems without S-curve integration.